Aliterella shaanxiensis (Aliterellaceae), a new coccoid cyanobacterial species from China - Zhang, Qi; Zheng, Lingling; Li, Tianli; Li, Renhui; Song, Lirong (Phytotaxa, 2018)
A new coccoid cyanobacterial species Aliterella shaanxiensis sp. nov. is described from a freshwater inland lake in Shaanxi Province, China. The new Aliterella species is defined by using a polyphasic approach that combines morphological, ultrastructural and ecological characteristics, as well as genetic analyses. It is morphologically similar to A. antarctica and A. atlantica but can be distinguished from the latter by its smaller cell, parietal thylakoids, freshwater habitat and 16S rRNA sequence difference. Phylogenetic analyses based on 16S rRNA sequence support the monophyly of the genus Aliterella. The novel taxa described in this study contribute to a better understanding of the diversity of the genus Aliterella in different habitats.